KELAYAKAN MEDIA BOOKLET SUBMATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Rukmana, Hartarti Indah; Syamswisna, Syamswisna; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the feasibility of media booklets on sub-material biodiversity in class X Senior High School in Kapuas Hulu. The present qualitative study employs descriptive method. The data collected on the booklet validation sheet is qualitative data. Each statement item is divided into categories Very Good is worth 4, Good is worth 3, Less Good is worth 2, and Not Good is worth 1. Since the data is in qualitative form, then to calculate it needs to be converted into a quantitative form using the Lawshe formula. Validation results from the validator can be analyzed using Content Validity Ratio (CVR) analysis. The booklet was validated its feasibility by two lecturer of Biology education program, Faculty of Education Untan and three Biology teacher of tenth grade students from three different school in Kapuas Hulu. According to the validator, the booklet is categorized as valid with validation average score 0,99 and it is worth to be implemented as instructional media on biodiversity utilization sub material.Â Keywords: Biodiversity, booklet, Kapuas Hulu